Use of region natural features in rural territories multipurpose development - Tarasenko, Nadezhda; Kriulina, Elena (Economics of Agriculture, 2018)
In article on the basis of the short climatic characteristic conditions is shown that, in the region there are rather serious preconditions for the rural territories organization multipurpose development, including rural population improvements, and rural tourism, under condition of creation in their borders a necessary infrastructure. Also potential directions of rural territories multipurpose development is examined by creating a health rehabilitation center. The basic directions of improvement and medical rehabilitation of rural population are defned on an example of Trunovsky area, typical rural municipal area of Stavropol Territory. It is given an annotation of natural medical factors of rural territories rational use. The main purpose is the search of fnancial possibilities of placing in Trunovsky area territory an inter-regional medical-improving complex which should become rural, using and developing advantages and possibilities of rural territory and rural tourism.